Evaluation of the solid waste management at the Hospital I El Buen Samaritano of Bagua Grande - Amazonas, 2014 - Santisteban Salazar, Nelson César (2016)
To describe solid waste production and management at the Good Samaritan Hospital of Bagua Grande in the Amazonas region of Peru, as well as knowledge regarding solid waste management among hospital staff, between July and December of 2014. Descriptive, cross sectional observational study. Data was collected through observations using structured guides and through interviews and a test applied to hospital staff. The observation guide and checklist used followed Peruvian Technical Standards of the Ministry of Health, the Leopold matrix for environmental impact assessment was used. We found a rate of waste generation of 2.56 kg / bed / day; The waste management was poor; knowledge about biosafety was regular to excellent in medical hospital staff, and poor among cleaning staff; The activities most harmful to the environment were infectious waste spills, incinerator use and discontinuous training, and the most affected environmental parameter was occupational health and safety. We conclude there is inadequate management of hospital waste because it does not comply with the national standards on sanitary waste management.